Derivation of Mesenchymal Stromal Cells from Ovine Umbilical Cord Wharton's Jelly. Issue 1 (20th January 2021) - Carreras‐Sánchez, Irene; López‐Fernández, Alba; Rojas‐Márquez, Raquel; Vélez, Roberto; Aguirre, Màrius; Vives, Joaquim
Abstract: The methods described herein allow for the isolation and expansion of fibroblastic‐like ovine Wharton's jelly‐derived mesenchymal stromal cells (oWJ‐MSC) that, similarly to their human counterparts, adhere to standard plastic surfaces in culture; show a mesenchymal profile for specific surface antigens (i.e., positive for CD44 and CD166); and lack expression of endothelial (CD31) and hematopoietic (CD45) markers as well as major histocompatibility complex (MHC) class‐II. Homogeneous cell cultures result from a two‐phase bioprocess design that starts with the isolation of mesenchymal stromal cells (MSC) from the Wharton's jelly of ovine umbilical cords up to a first step of cryopreservation. The second phase allows for further expansion of ovine WJ‐MSC up to sufficient numbers for further studies. Overall, this methodology encompasses a 2‐week bioprocess design that encompasses two cell culture passages ensuring sufficient cells for the generation of a Master Cell Bank. Further thawing and scale expansion results in large quantities of oWJ‐MSC that can be readily used in proof of efficacy and safety studies in the preclinical development stage of the development of cell‐based medicines. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Isolation and expansion of ovine mesenchymal stromal cells from Wharton's jelly of the umbilical cord Basic Protocol 2 : Characterization of ovine mesenchymal stromal cells Basic Protocol 3 : Growth profile determination of ovine mesenchymal stromal cells from Wharton's jelly